Information Systems Research in Vietnam A Shared Vision and New Frontiers - Hoang Thuan, Nguyen; Dang-Pham, Duy.; Le, Hoanh-Su.; Phan, Tuan Q. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book provides a collection of advanced information systems research, cases and applications in the context of Vietnam, presented by experienced researchers in the field. It provides a comprehensive overview of the field and offers access to practical information systems applications, serving as a guide to comparing the context. Readers can also compare the context of information systems applications in Vietnam as a developing country against the context in developed countries. The book contributes to the body of knowledge in several ways. It provides comprehensive references for information systems research, promotes the recent progress in its applications in Vietnam and offers a shared understanding to serve as a blueprint for future research. From a practical point of view, the book helps organisations/companies in Vietnam to keep up with information systems cases, studies and applications.
Part 1. Emerging Information Systems Research -- Chapter 1. Emerging Management Information Systems -- Chapter 2. Emerging Information Systems Applications -- Chapter 3. Advances in Big Data and Applications -- Chapter 4. Advances in Industry 4.0 and Smart City -- Chapter 5. Blockchain and Applications -- Chapter 6. Business Process Modelling and Applications -- Chapter 7. New Frontiers of Information Systems in context of Vietnam -- Part 2. Information Systems Cases -- Chapter 8. Case studies on how Vietnamese organisations respond to disruptive technologies -- Chapter 9. Case studies and on IS usage on organisational activities -- Chapter 10. Case studies and discussions on generational IS trends -- Chapter 11. SI research comparing between the context of Vietnam and other countries -- Part 3. Digital Business and Transformation -- Chapter 12. How new and emerging digital technologies/services/information systems challenge existing businesses in Vietnam -- Chapter 13. Evaluating the impact ofdigital disruption on different functions in the organisations -- Chapter 14. Exploring how new information systems support digital business/digital transformation -- Chapter 15. Evaluation of how users accept or adapt to new information systems.
Keywords: Business information services; Application software; Business Information Systems; Computer and Information Systems Applications